MGL Ligand Expression Is Correlated to Lower Survival and Distant Metastasis in Cervical Squamous Cell and Adenosquamous Carcinoma - Sahasrabudhe, Neha M.; van der Horst, Joost C.; Spaans, Vivian; Kenter, Gemma; de Kroon, Cor; Bosse, Tjalling; van Vliet, Sandra J.; Jordanova, Ekaterina S. (Frontiers in Oncology, 2019)
Cervical cancer is the fourth most common cancer in women worldwide and is characterized by a highly immune-suppressive microenvironment. Here, we describe aberrant glycosylation as a factor mediating this immunosuppressive microenvironment. Strong expression, as determined by immunohistochemistry, of a specific carbohydrate ligand for the immune-regulatory C-type lectin macrophage galactose-type lectin (MGL) correlated to lymph node metastasis, poor disease-specific survival and distant recurrences in cervical squamous cell carcinoma (SCC) and adenosquamous carcinoma (ASC), but not in adenocarcinoma (AC). MGL ligand expression was also associated with the absence of CD14+ myeloid cells and the presence of CD14-CD163+ myeloid cells. The expression of the MGL receptor itself could be detected on these CD163+ cells by immunofluorescence, suggesting that MGL+ myeloid cells are able to interact locally with MGL ligand+ tumor cells. Additionally, MGL ligand expression correlated with the occurrence of PIK3CA mutations, the most frequently observed oncogenic alteration in cervical cancer. In conclusion, we present prognostic value for MGL ligand expression in SCC/ASC patients, which further supports an immune evasive role for the C-type lectin MGL in the tumor immune compartment.